TOLERANSI DAN PERDAMAIAN DALAM PERSPEKTIF KONSTITUSI DAN HAK ASASI MANUSIA - Dieni Puja Lestari, Fitha; Ayu Fatma Nur Shidiq, Azwar; Al-Ma’arif, Azhar; Wasikin; Haffan Syam, Alfad (STKIP Subang, 2026)
Diversity in Indonesia is a cultural asset guaranteed by the constitution, yet it frequently faces phenomena of intolerance that threaten national peace. This research aims to describe the legal foundation of tolerance in Indonesia and formulate solutions for maintaining peace through a human rights approach. The research method used is normative legal research with a library research type, employing statute and conceptual approaches. Secondary data consisting of primary and secondary legal materials were analyzed qualitatively using content analysis methods. The results show that tolerance from the perspective of the Indonesian constitution is a fundamental legal obligation enshrined in the 1945 Constitution, particularly Articles 28E, 29, and 28J. Positive peace can be achieved if there is a balance between the exercise of rights and the fulfillment of fundamental obligations, along with equality before the law. However, implementation is still hampered by unharmonized regional regulations and the weak firmness of the state in addressing intolerant practices. As a solution, harmonization of laws and regulations and strengthening the state's role as a neutral mediator in law enforcement are required to realize a tolerant and peaceful social order.